2020
DOI: 10.1186/s40792-020-01052-z
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid technique of virtual-assisted lung mapping and systemic indocyanine green injection for extended segmentectomy

Abstract: Background Various approaches have been used to assist and facilitate segmentectomy with favorable oncological outcomes. We describe a hybrid approach comprising virtual-assisted lung mapping (VAL-MAP), which is a preoperative bronchoscopic dye-marking technique, combined with systemic indocyanine green (ICG) injection. Clinical presentation An asymptomatic 64-year-old man was referred to our department because of a lung nodule detected during his annual medical checkup. The chest computed-tomography image r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…They found that intravenous ICG method was totally concordant with the modified inflation-deflation method. Finally, the benefit of a hybrid technique of VAL-MAP and systemic injection was recently demonstrated for a nodule deeply located between the left upper division segment and the left lingular segment (34). Ethical Statement: The authors are accountable for all aspects of the work in ensuring that questions related to the accuracy or integrity of any part of the work are appropriately investigated and resolved.…”
Section: Arterial Demarcationmentioning
confidence: 99%
“…They found that intravenous ICG method was totally concordant with the modified inflation-deflation method. Finally, the benefit of a hybrid technique of VAL-MAP and systemic injection was recently demonstrated for a nodule deeply located between the left upper division segment and the left lingular segment (34). Ethical Statement: The authors are accountable for all aspects of the work in ensuring that questions related to the accuracy or integrity of any part of the work are appropriately investigated and resolved.…”
Section: Arterial Demarcationmentioning
confidence: 99%
“…However, another concern may be lung volume wasting. Extended segmentectomy is an alternative to increase safety margins during pulmonary nodule resection [ 11 ]. We defined extended segmentectomy as segmentectomy with a wedge resection of a neighbor segment ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…When nodules are found in peripheral segments or intersegmental planes, it is critical to carefully consider the tumor location and segmental region to provide radical surgical margins. 9 In conclusion, accurate knowledge of the nodule and intersegmental plane is required to perform a successfully complex segmentectomy. While VAL-MAP was initially designed to aid in tumor localization, the hybrid approach employing VAL-MAP and systemic indocyanine green injection showed efficacy in enabling segmentectomy.…”
mentioning
confidence: 99%
“…When nodules are found in peripheral segments or intersegmental planes, it is critical to carefully consider the tumor location and segmental region to provide radical surgical margins. 9 …”
mentioning
confidence: 99%
See 1 more Smart Citation